The comparative effect of core stability exercise and aquatic exercise therapy on reducing pain in patients with low back pain - Haritsah, Nurul Fithriati; Handita W, Yoga; Basuki, Nur (Science Midwifery, 2024)
Low Back Pain (LBP) is a prevalent health issue caused by improper posture during activities, resulting in pain, stiffness, or muscle tension in the lower back (Minghelli, 2017). It is a major cause of disability, particularly among adults, and a common reason for seeking healthcare (Bento et al., 2019). The Indonesian Ministry of Health (2022) reports that 60-80% of the global population experiences at least one episode of LBP in their lifetime. This study used a pre- and post-test two-group design with random assignment. Group I received Core Stability Exercise therapy, while Group II received Aquatic Exercise Therapy. Both groups underwent treatment twice weekly for eight weeks. The study involved outpatients at KRMT Wongsonegoro Hospital, Semarang. Results: Core Stability Exercise significantly reduced pain in myogenic LBP patients (p=0.00). Aquatic Exercise Therapy also showed significant pain reduction (p=0.00). A significant difference was found between the two therapies (p=0.036), with Aquatic Exercise Therapy having a greater effect (mean=3.942) compared to Core Stability Exercise (mean=3.275). Core Stability Exercise and Aquatic Exercise Therapy both significantly reduce pain in myogenic LBP patients, with Aquatic Exercise Therapy being more effective.